Psychometric assessment of the marijuana adolescent problem inventory. (April 2018) - Knapp, Ashley A.; Babbin, Steven F.; Budney, Alan J.; Walker, Denise D.; Stephens, Robert S.; Scherer, Emily A.; Stanger, Catherine
Abstract: Cannabis is one of the most commonly used psychoactive substances among adolescents in the United States. Adolescent cannabis use has multiple consequences including academic, health, and psychiatric problems. The Marijuana Adolescent Problem Inventory (MAPI) is a 23-item scale adapted from the Rutgers Alcohol Problem Index and used in the current literature to assess cannabis use problem severity. Psychometric testing for the MAPI has yet to be reported. The current investigation assessed the psychometric characteristics of the MAPI with cannabis-using adolescents (n = 727) from school and outpatient settings who enrolled in five separate randomized clinical trials focused on treatment of substance use. Findings suggested that the MAPI is internally consistent and reliable. Factor structure analyses suggested that the MAPI measures one latent construct, with no differences in factor structure between the outpatient and school settings, supporting a one-factor model. External validity of the MAPI was also demonstrated as evidenced by significant relations with concurrent diagnosis of cannabis dependence and abuse, longitudinal frequency of cannabis use, and mean times used per day. Overall, this initial test of the psychometric characteristics of the MAPI suggests that it can be considered a reliable and valid measure of problems associated with cannabis use among adolescents. Future work is now needed to replicate these findings by testing the psychometric properties of the MAPI in more diverse samples and developing a short version to be used as a brief assessment tool. Highlights: Marijuana Adolescent Problem Inventory (MAPI) indexes cannabis use problem severity. Psychometric findings suggest that the MAPI is internally consistent and reliable. Factor structure analyses support a one-component solution. Initial tests suggest the MAPI is a promising measure to assess problem severity.